Teacher Well-Being Under Threat: The Consequences of Workplace Bullying from Preschool to Higher Education - António Portelada; Adelinda Candeias; Ana Lúcia João (Education Sciences)
Workplace bullying can be defined as the repeated occurrence of aggressive behaviour by one or more persons in a position of power towards the victim. This phenomenon remains insufficiently researched among education professionals, especially between different levels of education. With this in mind, the present study aims to assess and characterise this phenomenon in the Portuguese teacher population, as well as its consequences. A digital questionnaire was used for the study, which includes a socio-demographic component and two scales, namely the LIPT-60 scale and the WBMMS scale. The questionnaire was published online and made accessible to all teachers employed in schools in Portugal. The final sample consisted of 2003 teachers. The obtained results revealed that 22.5% of the sample acknowledged experiencing workplace bullying. The most prevalent aggressive behaviours included communication blockage and defamation and disregard for work. Vertical descent emerged as the most common form of bullying. More than half of the victims reported experiencing health issues, with a quarter of them requiring a medical certificate. Finally, we would like to emphasize the significance of this study as an initial step towards the prevention and reduction of workplace bullying among Portuguese teachers.